An Inclusive Model of Memory Work in Poland: Bridge to Poland as a Case Study - Jolanta Ambrosewicz-Jacobs (Ksiegarnia Akademicka Publishing, 2021)
The memory of World War II in Poland is sometimes plagued by an us/them mentality or a competition of suffering. This paper will attempt to answer several questions: how are non-Jews contributing to Holocaust memorialization in Poland today? How can recognizing this contribution serve to heal rifts and change deep-seated stereotypes? We will present a case study, based on participant observation, of Bridge To Poland, which emphasizes memory work conducted by non-Jewish Poles. Bridge To Poland’s latest project in conjunction with the Grodzka Gate-NN Theatre Centre, The Neshoma Project: Conversations with Poles Rescuing Jewish Memory, highlights those whom Tec calls “Rescuers of Memory”. Exposing people to their work, Tec believes, results in breaking down negative stereotypes about non-Jewish Poles and building bridges between people.